Unity in Environmental Design and Livable Neighborhood - Supoj Prompayuk; Nopadon Sahachaisaeree (My University, 2012)
The over resemblance of architectural features often creates a built-environment with monotonous and placelessness. This research attempts to examine the perception of both architects and non-architect persons on their perceptions over design element configurations. A set of simulated photographic stimuli embedded with relevant variables are utilized to persuade answers between two groups of respondents on their perceived unity in the neighborhood. The research suggested that, in order to create a united appearance, architect must pay close attention to wall color consistency and uniformity of roof and pavement color which could help create environmental harmony without boring side effects.
Keywords: Harmony (Music); Sense of Place; Environmental Psychology; Color perception and design